Working with African American and Latino Communities in the Wildland-Urban Interface - Cassandra Johnson; Martha C. Monroe (EDIS)
Revised! FOR-196, a 4-page illustrated fact sheet by Cassandra Johnson and Martha C. Monroe, focuses on the role of race, ethnicity, culture, and history in communication challenges in the interface. Includes references. Published by the UF School of Forest Resources and Conservation, July 2008.